Stroke in the Young Adults and Its Risk Factors — A Case-control Study (The Insight, 2023)
Introduction: Stroke is a complex pathological condition that results in brain impairment across many age groups.  In the past, stroke was predominantly considered a condition affecting older individuals but now it has revealed the occurrence of several stroke subtypes among young adults. Objective: The aim of this study was to determine the prevalence of stroke among the young adults and its risk factors. Method: This case-control study was conducted at the department of Neurology during January, 2021 to December, 2021 in Cox Bazar Medical College Hospital, Chattrogram, Bangladesh. Results: The mean age of the case group (n=58) was 23.31±2.01 years and 77.58% were male, 22.41% were female while in the control group (n=42), the mean age was 23.02±2.27 years and 50% were male and 50% were female. In the case group, .87.93% patients smoked, 93.10% had hypertension, 94.82% had diabetes, 13.79% had vasculitis, 20.68% had SLE, and 27.58% had cardiac arrhythmia while in the control group, 50% patients  smoked, 69.04% had hypertension, 54.76% had diabetes, 2.38% had vasculitis, 4.76% had SLE, and 0% had cardiac arrhythmia(p
Keywords: Stroke; young; adults; clinical; presentation; risk factors; CT scan